Preoperative perihilar cholangiocarcinoma assessment using virtual endoscopic imaging magnetic resonance cholangioscopy - Okuno, Mitsuru; Mukai, Tsuyoshi; Iwata, Shota; Tezuka, Ryuichi; Mita, Naoya; Uemura, Shinya; Iwashita, Takuji; Maruta, Akinori; Iwata, Keisuke; Tomita, Eiichi; Shimizu, Masahito (Endoscopy International Open, 2021)
Background and study aims Preoperative assessment of the superficial ductal spread (SDS) of perihilar cholangiocarcinoma (PCCA) is important for determining its resectability. A virtual endoscopic imaging method, magnetic resonance cholangioscopy (MRCS), wherein a three-dimensional image is created from magnetic resonance imaging (MRI) data, can evaluate all aspects of arbitrary bile ducts. Patients and methods Overall, 15 patients with PCCA who underwent preoperative MRI were enrolled. All patients underwent surgical treatment.Results MRCS could be performed based on preoperative MRI data in all patients. MRCS could not be used in one patient due to debris in the obstructed bile duct. The remaining 14 patients (93 %) were diagnosed with obstructed bile duct or irregular surface of the bile duct, signifying tumor invasion. The accuracy rate of diagnosing the SDS was 93 % (14/15). Seven patients underwent preoperative peroral cholangioscopy; the scope could not pass through the tumor in three patients. In these three patients, MRCS was able to be use dtoevaluate the obstructed side of the bile duct and faciliated accurate diagnosis of SDS.Conclusions MRCS can be used to noninvasively evaluate the bile duct in all directions. This novel method makes it easy to create virtual images and can be useful for diagnosing the preoperative SDS of PCCA.